Effects of Communities That Care on the Adoption and Implementation Fidelity of Evidence-Based Prevention Programs in Communities: Results from a Randomized Controlled Trial - Fagan, Abigail A. (2011)
This paper describes findings from the Community Youth Development Study (CYDS), a randomized controlled trial of the Communities That Care (CTC) prevention system, on the adoption and implementation fidelity of science-based prevention programming in 24 communities. Data were collected using the Community Resource Documentation (CRD), which entailed a multi-tiered sampling process and phone and web-based surveys with directors of community-based agencies and coalitions, school principals, service providers, and teachers. Four years after the initiation of the CTC prevention system, the results indicated increased use of tested, effective prevention programs in the 12 CTC intervention communities compared to the 12 control communities, and significant differences favoring the intervention communities in the numbers of children and families participating in these programs. Few significant differences were found regarding implementation quality; respondents from both intervention and control communities reported high rates of implementation fidelity across the services provided.